Editor’s Note - Terdudomtham, Thamavit (Journal of Contemporary Social Sciences and Humanities, 2025)
The aim of RJSH is to publish research work contributing to contemporary social sciences and humanities. We are excited to present to you in this issue eight research articles involving various academic disciplines and practical matters. In the first article, Sanu Mahatthanadull and Orachorn Kraichak used mixed-method research to study and develop a Buddhist model to enhance the emotional strength of professional nurses. The authors found the model, based on the Buddhist principle of the fourfold development, to be effective in generating a positive change in the mood and emotions of the nursing professionals who had participated in the workshops. In the second article, Chompoonuh Kosalakorn Permpoonwiwat and Uthai Krawglom conducted a survey to estimate the Willingness to Pay (WTP) for insurance fees of foreign tourists who visited Thailand for road safety and to reduce the risk of road accidents occurring among visitors. The research revealed findings about WTP among foreign tourists and the WTP value which was also acceptable to involved government and private agencies.